Faktor-Faktor yang Berhubungan dengan Kejadian Obesitas pada Mahasiswa Fakultas Ilmu Kesehatan Universitas Pembangunan Nasional “Veteran” Jakarta: Factors Associated with the Incidence of Obesity among College Students at Fakultas Ilmu Kesehatan Universitas Pembangunan Nasional “Veteran” Jakarta - Rahadian, Fairy Amara; Wahyuningsih, Utami; Simanungkalit, Sintha Fransiske (Universitas Airlangga, 2024)
Background: Obesity is a nutritional issue with an escalating prevalence. Riskesdas 2018 indicates that the adult obesity rate has reached 21,8%. College students are in a transitional phase from adolescence to adulthood, which necessitates adaptation to the academic environment that often lead to the development of unhealthy lifestyles. This issue causes college students susceptible to obesity due to risk factors, such as eating patterns, eating behavior, physical activity, and stress. Objectives: Analyzing factors associated with the incidence of obesity among college students at Fakultas Ilmu Kesehatan Universitas Pembangunan Nasional (FIKES UPN)